Proteolytic cleavage product of 30-kDa adipocyte complement-related protein increases fatty acid oxidation in muscle and causes weight loss in mice - Fruebis, Joachim (The National Academy of Sciences, 2001)
Adipocyte complement-related protein (30 kDa) (Acrp30), a secreted protein of unknown function, is exclusively expressed in differentiated adipocytes; its mRNA is decreased in obese humans and mice. Here we describe novel pharmacological properties of the protease-generated globular head domain of Acrp30 (gAcrp30). Acute treatment of mice with gAcrp30 significantly decreased the elevated levels of plasma free fatty acids caused either by administration of a high fat test meal or by i.v. injection of Intralipid. This effect of gAcrp30 was caused, at least in part, by an acute increase in fatty acid oxidation by muscle. As a result, daily administration of a very low dose of gAcrp30 to mice consuming a high-fat/sucrose diet caused profound and sustainable weight reduction without affecting food intake. Thus, gAcrp30 is a novel pharmacological compound that controls energy homeostasis and exerts its effect primarily at the peripheral level.